Applications for solar irradiance nowcasting in the control of microgrids: A review. (September 2021) - Samu, Remember; Calais, Martina; Shafiullah, G.M.; Moghbel, Moayed; Shoeb, Md Asaduzzaman; Nouri, Bijan; Blum, Niklas
Abstract: The integration of solar photovoltaic (PV) into electricity networks introduces technical challenges due to varying PV output. Rapid ramp events due to cloud movements are of particular concern for the operation of remote islanded microgrids (MGs) with high penetration of solar PV generation. PV plants and optionally controllable distributed energy resources (DERs) in MGs can be operated in an optimized way based on nowcasting, which is also called very short-term solar irradiance forecasting up to 60 min ahead. This study presents an extensive literature review on nowcasting technologies along with their current and future possible applications in the control of MGs. Ramp rates control and scheduling of spinning reserves are found to be the most recognized applications of nowcasting in MGs. An online survey has been conducted to identify the limitations, benefits and challenges of deploying nowcasting in MGs. The survey outcomes show that the incorporation of nowcasting tools in MG operations is still limited, though the possibility of increasing solar PV penetration levels in MGs if nowcasting tools are incorporated is acknowledged. Additionally, recent nowcasting tools, such as sky camera-based tools, require further validation under various conditions for more widespread adaptation by power system operators. Highlights: A comprehensive review of solar irradiance forecasting methods with their classification. Applications, benefits and limitations of nowcasting in microgrids (MGs) operations are outlined. Lessons learnt from an online survey on nowcasting applications in MGs are reported. PV hosting capacity can be increased in MGs if nowcasting tools are incorporated.